Postauricular Incision Versus Modified Blair Incision in Parotidectomy: A Systematic Review and Meta-Analysis. (April 2023) - Tsao, Yu-Ning; Ho, Che-Fang; Hsin, Li-Jen; Yang, Shih-Wei; Tsai, Yao-Te; Tsai, Ming-Shao; Lee, Yi-Chan
Objective: The mainstay of first-line treatment of parotid tumors is adequate surgical removal. The present study was conducted to compare the differences between parotidectomy with postauricular incision (PI) and modified Blair incision (MBI). Data Sources: A systematic search of PubMed, Embase and the Cochrane Library was performed. Methods: The data of interest and study characteristics were extracted from the included studies. Statistical analysis was performed with Comprehensive Meta-Analysis software (version 3; BioStat, Englewood, NJ). Dichotomous data and continuous data were analyzed by calculating the risk difference and the mean difference with the 95% confidence interval respectively. Results: Four retrospective studies were included in the present meta-analysis. The pooled results revealed that the cosmetic satisfaction score was higher in the PI group (MD = 2.67; 95% CI, 2.12 to 3.23) and that intraoperative blood loss was lower in the PI group (MD =  −55.35; 95% CI, −100.33 to −10.36). The operative duration (MD  =  −5.15; 95% CI, −24.06 to 13.75), tumor size (MD  =  −.07; 95% CI, −.27 to .13) and incidences of common postoperative complications were comparable between the two groups. Conclusions: According to these findings, the use of PI in parotidectomies may be one of the options for improving cosmetic outcomes. This technique may be considered if oncological safety can be secured.